Case report: Exposed midfoot fracture due to traffic accident in HIV/AIDS patient - Fernández-Villacorta, Freddy J. (2020)
Currently there is a high incidence of traffic accidents in the world, many of them cause severe disability in people. These limb injuries cause high morbidity even reaching an amputation. This is aggravated in HIV/AIDS patients, especially in treatment and evolution. A clinical case of a patient with severe midfoot injury that ends in amputation is presented and a surgical management review of the trauma patient with HIV/AIDS is made.